Early music : a very short introduction - Kelly, Thomas Forrest (New York : Oxford University Press, 2011)
From Gregorian chant to Bach's Brandenburg Concerti, the music of the Medieval, Renaissance, and Baroque periods is both beautiful and intriguing, expanding our horizons as it nourishes our souls. In this Very Short Introduction, Thomas Forrest Kelly provides not only a compact overview of the music itself, but also a lively look at the many attempts over the last two centuries to revive it. Kelly shows that the early-music revival has long been grounded in the idea of spontaneity, of excitement, and of recapturing experiences otherwise lost to us--either the rediscovery of little-known repert.
What does "early music" mean? -- Repertories: medieval -- Repertories: renaissance -- Repertories: baroque -- Performing issues -- The modern early music revival.
Includes bibliographical references (pages 123-124) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Performance practice (Music); Music -- Interpretation (Phrasing, dynamics, etc.); Music -- 500-1400 -- History and criticism; Music -- 15th century -- History and criticism; Music -- 16th century -- History and criticism; Music -- 17th century -- History and criticism; Pratique de l'exécution (Musique); Musique -- 500-1400 -- Histoire et critique; Musique -- 15e siècle -- Histoire et critique; Musique -- 16e siècle -- Histoire et critique; Musique -- 17e siècle -- Histoire et critique; Phrasé.; MUSIC -- History & Criticism; Performance practice (Music); Music -- Interpretation (Phrasing, dynamics, etc.); Music -- History and criticism. -- 500-1400.; Music -- History and criticism. -- 15th century; Music -- History and criticism. -- 16th century; Music -- History and criticism. -- 17th century; Music; Music -- Interpretation (Phrasing, dynamics, etc.); Performance practice (Music); Uitvoeringspraktijk; Oude muziek; 500-1699; dissertations; Criticism, interpretation, etc; Academic theses; Thèses et écrits académiques.